Development of an electric bike with BLDC motor drived by a converter based on MOSFET transistors and closed-loop current control - Rodrigues, Rafael (2024)
This paper presents the development of a prototype of a bicycle with an electric propulsion device. For the development of the prototype, design requirements were established to achieve some objectives, such as performance and energy savings. Starting from a conventional bicycle, without additional propulsion, it was proposed to include a BLDC (Brushless Direct Current) type electric motor, driven by a converter based on MOSFET's transistors and powered by a battery system that includes an energy management system and a microprocessor controller for measuring and controlling currents, voltages, and speed. The project mainly aims to apply existing technologies and concepts with the aim of developing a means of transport that is agile, easy to operate, and capable of achieving the desired performance.